Urinary viral shedding of COVID-19 and its clinical associations: A systematic review and meta-analysis of observational studies - Kashi, Amir H.; de la Rosette, Jean J. M. C. H.; Amini, Erfan; Abdi, Hamidreza; Fallah-Karkan, Morteza; Vaezjalali, Maryam (Urology and Nephrology Research Centre, 2020)
Objectives: To review the current literature on the presence of COVID-19 virus in the urine of infected patients and to explore the clinical features that can predict the presence of COVID-19 in urine.Materials and Methods: A systematic review of published literature between 30th December 2019 and 21st June 2020 was conducted on Pubmed, Google Scholar, Ovid, Scopus, and ISI web of science. Studies investigating urinary viral shedding of COVID-19 in infected patients were included. Two reviewers selected relative studies and performed quality assessment of individual studies. Meta-analysis was performed on the pooled case reports and cohort with a sample size of >= 9.Results: Thirty-nine studies were finally included in the systematic review; 12 case reports, 26 case series, and one cohort study. Urinary samples from 533 patients were investigated. Fourteen studies reported the presence of COVID-19 in the urinary samples from 24 patients. The crude overall rate of COVID-19 detection in urinary samples was 4.5%. Considering case series and cohorts with a sample size of >= 9, the estimated viral shedding frequency was 1.18 % (CI 95%: 0.14 - 2.87) in the meta-analysis. Urinary viral load in most reports were lower than rectal or oropharyngeal samples. In adult patients, urinary shedding of COVID-19 was commonly detected in patients with moderate to severe disease (16 adult patients with moderate or severe disease versus two adult patients with mild disease). In children, urinary viral shedding of COVID-19 was reported in 4 children who all suffered from mild disease. Urinary viral shedding of COVID-19 was detected from day 1 to day 52 after disease onset. The pathogenicity of virus isolated from urine has been demonstrated in cell culture media in one study while another study failed to reveal replication of isolated viral RNA in cell cultures. Urinary symptoms were not attributed to urinary viral shedding.Conclusion: While COVID-19 is rarely detected in urine of infected individuals, infection transmission through urine still remains possible. In adult patients, infected urine is more likely in the presence of moderate or severe disease. Therefore, caution should be exerted when dealing with COVID-19 infected patients during medical interventions like endoscopy and urethral catheterization especially in symptomatic adult patients while in children caution should be exerted regardless of symptoms.
Keywords: COVID19; SARS-Cov2-; Urine; Review; Meta-Analysis; Infection Transmission